2022
DOI: 10.1302/2633-1462.312.bjo-2022-0111.r1
|View full text |Cite
|
Sign up to set email alerts
|

No time to waste; the impact of the COVID-19 pandemic on hip, knee, and shoulder arthroplasty surgeries in the Netherlands and Denmark

Abstract: Aims This study aimed to investigate the estimated change in primary and revision arthroplasty rate in the Netherlands and Denmark for hips, knees, and shoulders during the COVID-19 pandemic in 2020 (COVID-period). Additional points of focus included the comparison of patient characteristics and hospital type (2019 vs COVID-period), and the estimated loss of quality-adjusted life years (QALYs) and impact on waiting lists. Methods All hip, knee, and shoulder arthroplasties (2014 to 2020) from the Dutch Arthropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…With other factors contributing to more cancellations (for example, climate change, strikes, supply interruptions), the current number is expected to be even higher. Although data are scarce for other countries, similar patterns are expected 4 , 5 .…”
Section: Introductionmentioning
confidence: 54%
“…With other factors contributing to more cancellations (for example, climate change, strikes, supply interruptions), the current number is expected to be even higher. Although data are scarce for other countries, similar patterns are expected 4 , 5 .…”
Section: Introductionmentioning
confidence: 54%
“…Studies worldwide have found significant decreases in arthroplasty procedures due to the pandemic. [4][5][6][7][8][9][10][11][12][13][14][15] As an orthopedic surgery requiring substantial contact between the surgeon and the patient, new protocols to reduce the infection have negatively impacted arthroplasty. 15 Postponement or cancellation of elective operations was rampant during the pandemic, alongside stricter procedures and guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 caused by the SARS-CoV-2 virus had a tremendous effect on healthcare systems worldwide. Hospitals had to restructure to accommodate the influx of COVID-19 patients and prioritise acute care for non-COVID-19 patients, which disrupted orthopaedic care worldwide including reductions in elective and emergency surgical interventions,1–13 reduced clinic capacity3 4 6 10 12 and a decrease in orthopaedic trauma referrals and emergency admissions 6 7 12 14 15. Even more, the COVID-19 pandemic have led to an estimated total health loss for elective orthopaedic arthroplasty patients of approximately 30 000 QALYs, with decades of back-log of surgical capacity for these patients if capacity is not increased 13.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals had to restructure to accommodate the influx of COVID-19 patients and prioritise acute care for non-COVID-19 patients, which disrupted orthopaedic care worldwide including reductions in elective and emergency surgical interventions,1–13 reduced clinic capacity3 4 6 10 12 and a decrease in orthopaedic trauma referrals and emergency admissions 6 7 12 14 15. Even more, the COVID-19 pandemic have led to an estimated total health loss for elective orthopaedic arthroplasty patients of approximately 30 000 QALYs, with decades of back-log of surgical capacity for these patients if capacity is not increased 13. Many studies have described the impact of the COVID-19 pandemic on the volume of orthopaedic admissions,1–11 13 numbers of orthopaedic surgeries performed1–11 13 and the outcomes for COVID-19 patients admitted for orthopaedic care 16–20.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation